The concept of multi-criteria analysis of decision-making in the current system of health technology assessment in Russia - V. V. Omelyanovsky; V. K. Fedyaeva; N. Z. Musina (IRBIS LLC, 2018)
In the article, we analyze the current version of Government Regulation No. 871 where the principles of health technologies assessment (HTA) and the reimbursement strategies in Russia have been put forward. We conclude that the HTA methodology in Russia is consistent with the multi-criteria decision analysis. Recommendations on the improvement of the assessment methodology in Regulation No. 871 are provided.